Interaction between Epipompilus platensis (Hymenoptera: Pompilidae) and Ariadna mollis (Araneae: Segestridae) - Gabellone, Cecilia Sofía (2020)
In the present study, data on the interaction between wasp specimens of the species Epipompilus platensis Roig Alsina, 2017 (Hymenoptera, Pompilidae) and spiders of the species Ariadna mollis (Holmberg 1876) (Araneae, Segestriidae) are presented for the first time. Present in the localities of Punta Lara (Partido de Ensenada) and José Hernández (Partido de La Plata), both belonging to the province of Buenos Aires. Several specimens of A. mollis were collected on april 2015, and those that presented an egg or a small larva attached to the back of the abdomen were selected. They were kept under observation in a bioterium until completing the development of the wasp's adult state. Of the total spiders collected, 9.6% were parasitized by wasps. Of that percentage, four larvae of E. platensis reached the adult stage (three females and one male). The results obtained contribute to the knowledge of a new interaction between wasps and spiders.